Performance of ground penetrating radar employing buffer-layered antennas for groundwater detection based on frequency scaling model / F. Farihas and I. Pasya - Farihas, F.; Pasya, I. (UiTM Press, 2020)
Groundwater detection using classical electromagnetic (EM) wave ground penetrating radar (GPR), which utilizes single-input single-output (SISO) antenna configuration in open-air condition, results in poor signal propagation through soil. This paper proposes groundwater detection using enhanced GPR system utilizing buffer-layered antennas, where an additional medium is placed between the antenna and the ground, acting as a matching layer. The performance of the proposed scheme is investigated using frequency-domain time-domain (FDTD) based numerical simulation. Typically, numerical GPR simulation using real measurement parameters requires large number of meshing and therefore takes longer time to perform and is run on computers with high specification. In this paper, comparison between simulations using real scale and frequency scale model is also presented. Simulation result indicates improvement in wave propagation inside homogeneous soil using buffer-layered antenna, which can be observed in both real scale and frequency scale simulations.